2021
DOI: 10.47176/mjiri.35.78
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequality in noncommunicable diseases: Results from a baseline Persian cohort study

Abstract: Background aimed to determ Methods: Th component ana at 95% confide Results: A to paramnesia (-0. (-0.046), recur (0.298). Furthe Conclusion: more concentra decrease the bu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Furthermore, in accordance with our findings, the prevalence of lung diseases was found to be disproportionately higher among individuals with low SES, thus indicating the presence of pro‐poor inequality. This observation aligns with the results of prior investigations conducted in similar contexts 17,33 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, in accordance with our findings, the prevalence of lung diseases was found to be disproportionately higher among individuals with low SES, thus indicating the presence of pro‐poor inequality. This observation aligns with the results of prior investigations conducted in similar contexts 17,33 …”
Section: Discussionsupporting
confidence: 93%
“…After calculating the SES score, people were divided into five quartiles. q1 and q2 placed as poor group, q3 middle, and q4 and q5 were placed in the rich group 17 …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, similar results were obtained in a study about diabetes treatment coverage in 55 low- and middle-income countries, in which Iran and some other Middle Eastern countries were also included. The results of that study showed that there was a gradient of greater treatment coverage with increasing household wealth [ 44 ]. Eventually, findings from a study on socioeconomic inequalities for non-communicable diseases in Fasa, southern Iran, and one on socioeconomic inequalities in risk factors for non-communicable diseases in Kurdistan, western Iran, showed significant socioeconomic inequalities in diabetes and its risk factors in these regions [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wealth score index (WSI) was estimated by performing multiple correspondence analysis (MCA) on the following variables: access to a freezer, washing machine, dishwasher, vacuum cleaner, computer, internet, motorcycle, car (no access, access to a car with a price of <50 million Tomans (national currency in Iran), and access to a car with a price of >50 million Tomans), color TV type (no color Tv or regular color Tv vs. Plasma color Tv), owning a cell phone, PC or laptop, international trips in lifetime (never, just pilgrimage, both pilgrimage or non-pilgrimage trips) [ 19 , 20 ]. Then the participants were stratified into five quantiles in terms of WSI; individuals in the first quantile had the highest socio-economic status and those in the fifth quantile had the lowest socio-economic status.…”
Section: Methodsmentioning
confidence: 99%